2015
DOI: 10.3390/f6041256
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Atmospheric CO2 Affects Ectomycorrhizal Species Abundance and Increases Sporocarp Production under Field Conditions

Abstract: Anthropogenic activities during the last century have increased levels of atmospheric CO2. Forest net primary productivity increases in response to elevated CO2, altering the quantity and quality of carbon supplied to the rhizosphere. Ectomycorrhizal fungi form obligate symbiotic associations with the fine roots of trees that mediate improved scavenging for nutrients in exchange for a carbohydrate supply. Understanding how the community structure of ectomycorrhizal fungi is altered by climate change is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…; Bílý Kříž [Godbold et al. ]). The study sites were selected because the three species are representative of the most common types of European deciduous and coniferous species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bílý Kříž [Godbold et al. ]). The study sites were selected because the three species are representative of the most common types of European deciduous and coniferous species.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was applied to three different even-aged, managed, European forests: an adult (80 yr old), Danish, temperate, European, beech forest (Fagus sylvatica L.; Sorø [Pilegaard et al 2011]), a moderately young (28 yr old), Finnish, boreal, Scots pine forest (Pinus sylvestris L.; Hyyti€ al€ a Bonosi 2001, M€ akel€ a et al 2006]) and a young (16 yr old), Czech, temperate-humid, Norway, spruce forest (Picea abies Karst. ; B ıl y K r ı z [Godbold et al 2015]). The study sites were selected because the three species are representative of the most common types of European deciduous and coniferous species.…”
Section: Study Sitesmentioning
confidence: 99%
“…In a number of ecosystems, the main effects of elevated atmospheric CO 2 on the fungal community have been found to be related to an increased allocation of plant photosynthetic C directed to roots and root-associated fungi (Treseder, 2004;Drigo et al, 2008;Staddon et al, 2014). Fine roots translocate C into the soil, influencing the composition of fungal communities associated with living roots of specific plant species (Treseder & Allen, 2000;Fransson et al, 2001;Gamper et al, 2004;Parrent et al, 2006;Godbold et al, 2015). Such changes, together with reported increases in microbial activity and thus CO 2 efflux under elevated CO 2 (Dieleman et al, 2012;Hagedorn et al, 2013), can potentially speed up the cycling of organic C belowground.…”
Section: Introductionmentioning
confidence: 99%
“…The change in ectomycorrhizal community structure under high CO 2 is often shown as a change in the abundance of dominant taxa (Fransson et al 2001;Godbold et al 2015) and has been related to changes in the supply of C to roots (Parrent and Vilgalys 2007). Recently, Clemmensen et al (2015) showed that productivity of Picea abies was a factor most strongly related to changes in fungal community composition.…”
Section: Distribution and Diversity Of Mycorrhizasmentioning
confidence: 99%
“…Several factors that increase tree productivity have been shown to change community structure of ectomycorrhizas; these include elevated CO 2 (Fransson et al 2001;Godbold et al 2015), defoliation (Pestana and Santolamazza-Carbone 2011), and stem harvesting (Jones et al 2010). The change in ectomycorrhizal community structure through all of these factors is linked to changes in C allocation to roots (Godbold et al 2015).…”
Section: Introductionmentioning
confidence: 99%